Tanggung Jawab Negara dalam Perlindungan Konsumen Digital di Era Kewarganegaraan Global: Analisis Hukum dan Etika Transnasional 2020–2025 - Zakia Lutfiah Khoirun Nisa; Izzul Nurdin Setyawan; Siti Khotijah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid growth of global digital technology has significantly reshaped social, economic, and legal systems. This transformation presents new challenges for states in fulfilling their legal responsibilities toward digital consumer protection amid the emergence of global citizenship. This study aims to analyze the forms of state responsibility in protecting digital consumer rights through legal and transnational ethical perspectives. Using a normative juridical method with conceptual and statutory approaches, this research focuses on national legal instruments such as Indonesia’s Personal Data Protection Act No. 27 of 2022 and regional policies such as the ASEAN Digital Framework Agreement 2025. The findings reveal that states bear dual responsibilities: protecting citizens’ digital rights domestically and adhering to international norms globally. This responsibility involves law enforcement against data violations, policy harmonization, and the strengthening of digital ethics. The study concludes that cross-border cooperation and ethical integration are essential to ensure fair and sustainable digital governance.